A Low-Cost Transcutaneous Electrical Nerve Stimulation Measuring Device Using Frequency-to-Voltage and Current-to-Voltage - Alfita Kurniawati; Torib Hamzah; Tri Bowo Indrato (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2020)
The use of transcutaneous electrical nerve stimulation (TENS) therapeutic devices to reduce the complexity of the patients continuing can cause an increase in the performance of the tool. The purpose of this study is to design a tool to calibrate TENS. The contribution of this study is the ease of users when performing TENS calibration because it can display the shape of the signal, the frequency value in units of Hz, as well as the current value in units of mA directly. To match the frequency and current according to the position of the red electrode cable, it must be higher than the position of the black electrode cable. The frequency-to-voltage that is changed then entered is converted into a voltage to be processed using Arduino. Then also with the current-to-voltage, which changes the inrush current and then is converted into a voltage to be processed using Arduino. The results showed that the frequency values ​​in all settings had an average error of 0.018, while the average error of the current in all settings was 0.25. At the frequency, a measurement obtained highest uncertainty value of UA is 1.6, UB is 0, and the highest U95 is 6.88 while in the current measurement obtained, the highest uncertainty value of UA is 0.19, UB is 0, and highest U95 is 0.392. The results of this study can be applied to the field of calibration, specifically the TENS therapy instrument calibration.